Determination of information requirements in the waiver of bidding: analysis at public universities in the state of alagoas (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This research analyzed information management in bidding waivers, in the period of the Covid-19 pandemic, in public universities in the State of Alagoas. Procedurally, this is a descriptive research, operationalized via multiple case studies, comprising the State University of Alagoas, the State University of Health Sciences of Alagoas and the Federal University of Alagoas. It considers the importance of educational institutions in promoting the wide dissemination of information about their purchases and hiring, including about exemptions from tenders, with transparency and reliability in society.
Keywords: access to information; exemption from bidding; information management; public universities in the State of Alagoas